CD27 stimulation unveils the efficacy of linked class I/II peptide vaccines in poorly immunogenic tumors by orchestrating a coordinated CD4/CD8 T cell response. (2nd December 2018) - Riccione, Katherine A.; He, Li-Zhen; Fecci, Peter E.; Norberg, Pamela K.; Suryadevara, Carter M.; Swartz, Adam; Healy, Patrick; Reap, Elizabeth; Keler, Tibor; Li, Qi-Jing; Congdon, Kendra L.; Sanchez-Perez, Luis; et al.
ABSTRACT: Despite their promise, tumor-specific peptide vaccines have limited efficacy. CD27 is a costimulatory molecule expressed on CD4 + and CD8 + T cells that is important in immune activation. Here we determine if a novel CD27 agonist antibody (αhCD27) can enhance the antitumor T cell response and efficacy of peptide vaccines. We evaluated the effects of αhCD27 on the immunogenicity and antitumor efficacy of whole protein, class I-restricted, and class II-restricted peptide vaccines using a transgenic mouse expressing human CD27. We found that αhCD27 preferentially enhances the CD8 + T cell response in the setting of vaccines comprised of linked class I and II ovalbumin epitopes (SIINFEKL and TEWTSSNVMEERKIKV, respectively) compared to a peptide vaccine comprised solely of SIINFEKL, resulting in the antitumor efficacy of adjuvant αhCD27 against intracranial B16.OVA tumors when combined with vaccines containing linked class I/II ovalbumin epitopes. Indeed, we demonstrate that this efficacy is both CD8- and CD4-dependent and αhCD27 activity on ovalbumin-specific CD4 + T cells is necessary for its adjuvant effect. Importantly for clinical translation, a linked universal CD4 + helper epitope (tetanus P30) was sufficient to instill the efficacy of SIINFEKL peptide combined with αhCD27, eliminating the need for a tumor-specific class II-restricted peptide. This approach unveiled the efficacy of a class I-restricted peptide vaccine derived from the tumor-associated Trp2 antigen in mice bearing intracranial B16 tumors. CD27 agonist antibodies combined with peptide vaccines containing linked tumor-specific CD8 + epitopes and tumor-specific or universal CD4 + epitopes enhance the efficacy of active cancer immunotherapy.